Pola menonton televisi sebagai faktor risiko obesitas pada anak di sekolah dasar Kota Yogyakarta dan Kabupaten Bantul - Dewi Astiti; Hamam Hadi; Madarina Julia (Jurnal Gizi dan Dietetik Indonesia (Indonesian Journal of Nutrition and Dietetics), 2013)
ABSTRACTBackground: Obesity in Indonesian school children is increasing dramatically especially in the cities. Whether TV viewing has an important role to the increased obesity prevalence Indonesia is still unclear. Objective: To examine TV viewing as a risk factor of obesity in Indonesian elementary school children.Method: A case-control study of 244 obese and 244 non obese children was conducted in Yogyakarta municipality in 2012. Cases were elementary school children with BMI/Age >95 percentile identiﬁ ed in previous survey. Controls were children from the same class and seating at the right side nearest to the cases. Weight of the children was measured using a calibrated digital weighing scale (SECA) with precision of 0.1 kg, while standing height was measured using a microtoice with precision of 0.1 cm by trained nutritionists. Data on TV viewing were collected using one-week physical activity recall questionnaires. BMI of the study subjects were computed using WHO Anthro2005 software. Statistical analysis was done using STATA 11th edition software.Result: Children with TV viewing ≥2 hours/day were 3 (OR=3.3, 95%CI:  2.2-4.8) times more likely to be obese than children with TV viewing <2 hours/day. Parental regulation of tv viewing was associated with  child’s TV viewing duration.Conclusion: Duration of TV viewing was signiﬁ cantly associated with the increased risk of obesity in elementary school children. The existence of parental regulation would help to reduce TV viewing duration leading to the reduction of obesity prevalence in school children.KEYWORDS: obesity, elementary school children, TV viewingABSTRAKLatar Belakang: Obesitas pada anak-anak sekolah Indonesia meningkat sangat drastis terutama di kota-kota. Apakah menonton TV memiliki peran penting terhadap peningkatan prevalensi obesitas Indonesia masih belum jelas.Tujuan: Untuk menguji menonton TV sebagai faktor risiko obesitas pada anak-anak sekolah dasar di Indonesia.Metode: Sebuah studi kasus-kontrol dari 244 obesitas dan 244 anak non obesitas dilakukan di Kota Yogyakarta pada tahun 2012. Kasus adalah anak-anak SD dengan BMI/Umur >persentil ke-95 diidentiﬁ kasi dalam survei sebelumnya. Kontrol adalah anak-anak dari kelas yang sama dan duduk di sisi kanan terdekat dengan kasus. Berat anak-anak diukur dengan menggunakan timbangan digital (SECA) yang telah dikalibrasi dengan presisi 0,1 kg, sedangkan tinggi berdiri diukur dengan menggunakan microtoice dengan presisi 0,1 cm oleh ahli gizi terlatih. Data menonton TV dikumpulkan menggunakan kuesioner aktivitas ﬁ sik selama satu minggu. BMI dari subjek penelitian dihitung dengan menggunakan software WHO Anthro 2005. Analisis statistik dilakukan dengan menggunakan perangkat lunak STATA edisi 11.Hasil: Anak-anak yang menonton TV ≥ 2 jam / hari cenderung 3 (OR = 3,3, 95% CI: 2,2-4,8) kali lebih gemuk daripada anak-anak dengan menonton TV <2 jam/hari. Peraturan orangtua menonton TV dikaitkan dengan durasi menonton TV anakKesimpulan: Durasi menonton TV secara bermakna dikaitkan dengan peningkatan risiko obesitas pada anak-anak sekolah dasar. Adanya peraturan orangtua akan membantu mengurangi durasi menonton TV yang mengarah ke pengurangan prevalensi obesitas pada anak-anak sekolah.KATA KUNCI: obesitas, anak-anak SD, menonton TV